2016
DOI: 10.21164/pomjlifesci.39
|View full text |Cite
|
Sign up to set email alerts
|

Częstość Występowania Oraz Czynniki Skorelowane Z Bólem Miesiączkowym U Zdrowych Studentek

Abstract: Introduction: Menstrual disorders generally affect the daily activities of females, and menstrual pain is a common gynaecological complaint in westernized societies. The aim of the study was to determine the prevalence of, and the factors related to, menstrual pain in young, healthy women.Material and methods: Data from 600 university students were obtained during the cross sectional survey. Students were asked to complete an anonymous questionnaire. Information on the women’s socioeconomic status, age at mena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
1
1
Order By: Relevance
“…Teul et al showed that back pain is associated with painful menstruation, as it was significantly less frequent in the group with painless menstruation [39]. Similar conclusions were drawn by Knapik et al, who showed the presence of menstrual-related back pain in 8.6% of all menstruating girls covered by the study [40], which is not consistent with the results of this study.…”
Section: Discussioncontrasting
confidence: 48%
“…Teul et al showed that back pain is associated with painful menstruation, as it was significantly less frequent in the group with painless menstruation [39]. Similar conclusions were drawn by Knapik et al, who showed the presence of menstrual-related back pain in 8.6% of all menstruating girls covered by the study [40], which is not consistent with the results of this study.…”
Section: Discussioncontrasting
confidence: 48%
“…Treatment of the syndrome is pharmacological: use of inhibitors of prostaglandin synthetase (ibuprofen, naproxen) and oral contraception. Supplementation of vitamin B, E and magnesium can be introduced [4,9,19,20].…”
Section: Other Non-classified Menstrual Disordersmentioning
confidence: 99%